Sleep and performance in elite combat and contact athletes - Dunican, I. C. (The University of Western Australia, Centre for Sleep Science, School of Human Sciences, 2017)
Sleep is increasingly recognised as being an essential component of performance and recovery in elite athletes. Sleep may be negatively affected during training and competition as a result of factors such as the use of ergogenic aids including caffeine, the evening use of electronic devices and the potential presence of sleep disorders, all of which can also affect cognition, alertness and physical performance of athletes.